2011
DOI: 10.1163/156855411x615075
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Capacity of RC Beams Strengthened in Shear with Side-Bonded FRP Reinforcements Using Artificial Neural Networks

Abstract: The application of artificial neural network (ANN) to predict the shear capacity of reinforced concrete (RC) beams retrofitted in shear by means of side-bonded fiber-reinforced polymer (FRP) is investigated in this paper. An extensive literature review has been carried out. In addition, ten shear deficient RC beams with different carbon fiber-reinforced polymer (CFRP) configurations were tested and added as data to the collected data. It was aimed to build an efficient and practical ANN model with parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The newly developed models outperformed the prediction capacities of the other models. In a separate study, Tanarslan employed an ANN to predict the shear strength of concrete beams retrofitted with a side-bonded FRP [38]. Tanarslan reported good conformance with the experimental results, and the predictions were more accurate than those obtained using the theoretical guidelines.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The newly developed models outperformed the prediction capacities of the other models. In a separate study, Tanarslan employed an ANN to predict the shear strength of concrete beams retrofitted with a side-bonded FRP [38]. Tanarslan reported good conformance with the experimental results, and the predictions were more accurate than those obtained using the theoretical guidelines.…”
Section: Introductionmentioning
confidence: 86%
“…Based on the results and observations of their investigation researchers proposed modification to the design equations suggested by ACI for the evaluation of the shear capacity of beams strengthened with FRP. Tanarslan [38] evaluated the potential of ANN in predicting the shear strength of RC beams strengthened in shear with side-bonded FRP reinforcements. In addition to the dataset collected from literature, experimental testing of ten shear deficient beams with different carbon fibre reinforced polymer (CFRP) arrangements were conducted and the results were added.…”
Section: Sanad and Sakamentioning
confidence: 99%
“…They also presented design equations to calculate the shear capacity of FRP-strengthened RC beams in shear [49]. Tanarslan (2011) investigated the performance of ANN in predicting the shear capacity of the RC beams retro tted in shear by means of side-bonded FRP; obtained results demonstrated the higher accuracy of those values obtained by ANN [50]. Tanarslan et al (2012) used the back propagation network to determine the shear strength contribution of RC beams strengthened in shear by retro tting externally bonded wrapped and U-jacketed FRP reinforcement, and showed that ANN was a good tool for predicting [51].…”
Section: Prediction Based On Soft Computingmentioning
confidence: 99%